The Effect of Solvency Ratios on Stock Prices in Automotive Subsector Companies Listed on the Indonesia Stock Exchange during 2019–2023 - Putri, Ratu Salmuna Mutiara; Kosasih, Kosasih; Hendriyani, Rina Maria; Manda, Gusganda Suria (Jurnal Ekuilnomi, 2026)
This study aims to analyze the effect of the Debt to Asset Ratio (DAR) and Debt to Equity Ratio (DER) on stock prices of automotive subsector companies listed on the Indonesia Stock Exchange (IDX) during the 2019–2023 period. This research employed a quantitative method with purposive sampling, using secondary data consisting of annual financial statements and stock price information obtained from official IDX publications. The data were analyzed using multiple linear regression with classical assumption tests, t‐tests, and F‐tests. The results indicate that DAR has a positive and significant effect on stock prices, while DER has a negative and significant effect on stock prices. Furthermore, DAR and DER simultaneously exert a significant influence on stock prices. These findings highlight that capital structure, as reflected by DAR and DER, plays an important role in determining stock price movements in the automotive subsector